Extracellular vesicles from Aggregatibacter actinomycetemcomitans exhibit potential antitumorigenic effects in oral cancer: a comparative in vitro study - Marjut Metsäniitty; Shrabon Hasnat; Carina Öhman; Tuula Salo; Kari K. Eklund; Jan Oscarsson; Abdelhakim Salem (2024)
Abstract Aggregatibacter actinomycetemcomitans is an opportunistic Gram-negative periodontopathogen strongly associated with periodontitis and infective endocarditis. Recent evidence suggests that periodontopathogens can influence the initiation and progression of oral squamous cell carcinoma (OSCC). Herein we aimed to investigate the effect of A. actinomycetemcomitans -derived extracellular vesicles (EVs) on OSCC cell behavior compared with EVs from periodontopathogens known to associate with carcinogenesis. EVs were isolated from: A. actinomycetemcomitans and its mutant strains lacking the cytolethal distending toxin (CDT) or lipopolysaccharide (LPS) O-antigen; Porphyromonas gingivalis ; Fusobacterium nucleatum ; and Parvimonas micra . The effect of EVs on primary and metastatic OSCC cells was assessed using cell proliferation, apoptosis, migration, invasion, and tubulogenesis assays. A. actinomycetemcomitans -derived EVs reduced the metastatic cancer cell proliferation, invasion, tubulogenesis, and increased apoptosis, mostly in CDT- and LPS O-antigen-dependent manner. EVs from F. nucleatum impaired the metastatic cancer cell proliferation and induced the apoptosis rates in all OSCC cell lines. EVs enhanced cancer cell migration regardless of bacterial species. In sum, this is the first study demonstrating the influence of A. actinomycetemcomitans- derived EVs on oral cancer in comparison with other periodontopathogens. Our findings revealed a potential antitumorigenic effect of these EVs on metastatic OSCC cells, which warrants further in vivo investigations.